Atração de investimentos como instrumento de política industrial: o caso do ceará no período 1985-2002 - Nunes, André de Castro Pereira (2005)
This paper aims to assess the performance of credit and fiscal mechanisms in attracting industrial investment to the state of Ceará during 1985-2002, a period characterized by the political and administrative continuity which begun with the implementation of the so-called 'Plan of Changes', during the term in office of former state governor Tasso Jereissati. In order to accomplish that, a survey was conducted of the state's credit, fiscal and infrastructure incentive mechanisms, industrial policy and the period's political context, as well as data from the Department of Industry and Commerce and on the economic performance of the state of Ceará. Over 700 industrial businesses were found to have been attracted into the state by means of the Industrial Investment Attraction Program, which amounted to a process of industry expansion while the country as a whole was going through a period of deindustrialization. The analysis points out that, if on one hand, the industrialization model then adopted was able to generate economic growth, on the other hand, it increased income concentration and could not drive industry into the less developed areas across the state's interior, as expected by Ceará's state government officials.